Situational Action Theory's Self-Control/Morality Interaction Effects and the Moderating Influence of Being Female: A Comparison of Property and Violent Offending Using a Sample of Juvenile Delinquents. (October 2019) - Ishoy, Glen A.; Blackwell, Brenda Sims
This study tests the interaction effects between self-control and morality that are proposed by situational action theory (SAT) and examines the ability of biological sex to condition those processes for both property and violent offending. This study employs negative binomial regression to analyze data from the Pathways to Desistance data set ( n = 1, 354). Results generally support the posited general nature of SAT for violent offending. The results for property offending were also supported; however, some of the results indicated that sex may moderate the associations of SAT's key variables for this offense type. Our results indicate that the assumption of generalizability across the sexes may be less problematic for SAT than for other theories, but more work is needed to fully articulate how sex affects the processes at work in the theory.